SMYD2 promotes cervical cancer growth by stimulating cell proliferation - Jun-Jie Sun; Hong-Lin Li; Hui Ma; Yang Shi; Li-Rong Yin; Su-Jie Guo (Cell & Bioscience, 2019)
Abstract Background Cervical cancer is the most common gynecological malignancy with low terminal cure rate, and therefore new therapeutic targets are urgently needed to combat this disease. SMYD2, as an oncogene, is abnormal highly expressed in multiple types of tumors and further affects the occurrence and development, but the potential correlations between SMYD2 expression and cervical cancer progression is still unclear. Methods We first used the bioinformatics website to screen the data of cervical cancer in (The Cancer Genome Atlas) TCGA and survival analysis was used to find the different survival rates in the SMYD2 high expression group and low expression group. Through immunohistochemistry, the association between SMYD2 expression and clinical-pathological features of cervical cancer patients was further evaluated. Quantitative PCR and Immunoblot were applied to investigate the relative mRNA and protein expression levels, respectively. In vivo and in vitro experiments were performed to explore the function of SMYD2 in cancer progression. Results We first found a high expression of SMYD2 in cervical cancer, and survival analysis found that the poorer survival rate in the SMYD2 high expression group than that in the low expression group. Herein, our study demonstrated that the expression of SMYD2 in patients with cervical cancer was associated with FIGO stage, tumor size and further correlated with poor prognosis. Our data further showed that the inhibition of SMYD2 expression in cervical cancer cell line Caski and Siha could dramatically block the proliferation of cervical cancer cells. Additionally, SMYD2-shRNA lentivirus infected remarkably inhibited tumorigenesis in mice compared with the scramble group. Conclusions Taken together, this study provides strong evidence of the involvement of SMYD2 in cervical cancer growth and indicates that it could have high potential as a therapeutic target of cervical cancer.